Plastics product design - Mastro, Paul F. (Scrivener Publishing ; Wiley, 2016)
This title is aimed at designers who have had limited or no experience with plastics materials as well as a more experienced designer who is designing a part for a use, process or an application that they are not familiar with. The reader is provided with an introduction to plastics as a design material and a discussion of materials commonly in use today.